Application of rhizobia and plant growth promoting Rhizobacteria for increased growth, N₂ fixation and yield of rice - Tan, Kee Zuan (2015)
Rice is one of the major foods consumed by people in most countries and especially from the Asian region, including Malaysia. Due to the ever-increasing demand, rice farmers tend to over-apply chemical fertilizers as the solution to increase the crop yield but this indiscriminate practice has a toll on the environment such as eutrophication due to fertilizer losses through leaching, volatilization and surface runoff. Biofertilizers have become prominent in the agricultural sector as an alternative source of nitrogen fertilizer and can substantially supplement the N requirement while enhancing the uptake of water and mineral nutrients of crop plants. Plant growth-promoting rhizobacteria (PGPR) have been reported to be beneficial to various crops including rice, while rhizobia are known for their symbiotic associations with legumes. There were reports on the benefits of rhizobial inoculation on rice but the mechanisms still remain unclear and are far more dynamic than previously thought. A series of studies involving six experiments were conducted to observe the effects of locally isolated PGPR and rhizobial strains in combined and single inoculations on growth, nitrogen fixation and yield of rice plants under laboratory and glasshouse conditions. In the preliminary study, isolation of PGPR and rhizobial strains from four locations of rice growing areas around Peninsular Malaysia with different cultural practices were undertaken. A total of 205 strains were obtained with the highest number of bacterial isolates from Besut, Terengganu (45%). This rice farming site practises minimal chemical fertilizer input system which is believed to promote plant-microbe interaction and increase beneficial activities to the host plant. It was also observed that higher numbers of endophytes compared to rhizospheric PGPR were isolated at sampling locations which have been cultivated with rice for a much longer period namely at Tunjung, Kelantan (61%) and Besut, Terengganu (56%). The microbial populations were believed to have developed mechanisms for survival by becoming root endophytes and consequently protected from adverse soil environmental conditions and competition with other indigenous soil microbes. The isolated PGPR and rhizobial strains were characterized through several biochemical assays namely biological nitrogen fixation, phosphate and potassium solubilization, and phytohormone, iron siderophore and hydrolyzing enzyme production. Two superior PGPR and two rhizobial strains were selected for subsequent experiments namely UPMB19, UPMB20, UPMR30 and UPMR31 and identified as Lysinibacillus xylanilyticus, Alcaligenes faecalis, Bradyrhizobium japonicum and Rhizobium etli bv. mimosa, respectively, along with the reference strain, UPMB10, identified as Bacillus subtilis. These strains have high nitrogenase activities which ranged between 15.60 – 19.95 nmol C2H4 mL¯¹ h¯¹. It was also observed that bacterial abilities to solubilize phosphate were positively correlated to the incubation period and negatively correlated to the media pH. UPMB10 produced highest soluble P at 6 days after incubation (51.14 μg mL¯¹ P), while UPMR31 produced 61.87 μg mL¯¹ soluble P at 12 days after incubation. These strains were also able to produce phytohormone (indole-3 acetic acid, IAA) which ranged between 8.932 – 23.681 μg mL¯¹ and solubilize potassium at the rates between 10.70 – 14.15 mg L¯¹. An in vitro study demonstrated that these PGPR and rhizobial strains could effectively maintain a high population and produce phytohormones in the residual nutrient solution, with a significant enhancement of rice seedling heights and total dry weights. This initial study has demonstrated some positive effects of the locally isolated PGPR and indigenous rhizobial strains on the rice plant. In the glasshouse study with rice plants in 15 kg plastic pots, 33% of fertilizer-N supply from the conventional recommended rate was found to be optimum for bacterial inoculation treatment. In some cases, the growth and yield enhancements were even greater than the control plant with full fertilizer-N, suggesting the possibility that these bacterial inocula could be applied to minimize chemical fertilizer inputs while still producing higher yields compared to the conventional practice. It was also observed that tiller productions were positively correlated to the yield. Inoculation with UPMB19 resulted in a significantly more tillers (28) at 43 DAP and subsequently produced significantly higher spikelet weight (107 g) at terminal harvest (115 days after planting). The rhizobial strain, UPMR30, also performed better than other inoculants by producing significantly higher spikelet weights, directly correlated to rice grain yield. The final experiment was conducted to determine the effects of combined inocula which consisted of a selected PGPR (UPMB19) and rhizobia (UPMR30) on growth and N2 fixation of rice plant using 15N isotope dilution technique under glasshouse conditions for a 65 day-period. At the terminal harvest, the combined inocula successfully promoted rice plant top and root growth, tiller numbers, plant dry weights, nutrient accumulations in soil and plant tissues, and consequently increased the N2 fixation rate of the rice plant ecosystem. The rhizobia supplied nitrogen through BNF while the PGPR increased root proliferation and overall plant growth through the production of phytohormone (IAA). This was supported by the significantly higher values of chlorophyll and nitrogen content in plant tissues and dilutions of 15N a.e. % of the combined inocula and single inoculation with UPMR30 as compared to the single inoculation with UPMB19. The accumulation of N in the soil and plant tissues were also significantly increased in the inoculated plants and similar trends were observed with the reduction in 15N a.e. % as compared to the uninoculated control. This indicated that the BNF processes successfully increased the N availability around the roots for greater plant uptake. It was observed that the BNF activities of the rhizobial strain (UPMR30) was higher than the PGPR strain (UPMB19) with Ndfa values of 19 and 12%, respectively. Meanwhile, the combined inocula produced the highest BNF activities at 22% Ndfa, strongly suggesting a synergistic interaction and cumulative beneficial effects between the rhizobial and PGPR strains. Based on the BNF estimations, the combined inocula treatment could save up to 45% of fertilizer-N from the recommended rate for rice, equivalent to 63 kg N fixed ha¯¹ in the period of 65 days. Several co-inoculation studies have been undertaken by other researchers using rhizobial and PGPR strains. However, there has been no report regarding the multi-strain beneficial effects of BNF on rice involving combined applications of PGPR and rhizobia; thus, indicating the significance of this study.